Effects of yogic practices on physiological and biochemical parameters of hypertensive patients: A systematic review of clinical trials - Prakhar Tyagi; Khushbu Jain (Journal of Ayurveda and Integrative Medicine, 2025)
Background: Hypertension affects around 1.28 billion adults worldwide. If not managed properly, it can lead to life threatening conditions. While various pharmacological treatments are available, they are associated with various short- and long-term side effects. Hence it is crucial to explore alternative approaches to complement the standard medical interventions. Objective: This systematic review aims to explore the impacts of yogic practices on various physiological and biochemical parameters in hypertensive patients. Methods: Various electronic databases including PubMed, Cochrane library, Directory of Open Access Journals and Google scholar were systematically searched until October 31, 2023 to collect relevant data. Results: A total of 15 articles comprising 5 RCTs and 10 clinical trials were identified. The number of participants ranged between 33 and 300, with Yoga intervention lasting from two months to a year. The analyses revealed that Yogic practices, such as loosening practices, Surya Namaskar, Tadasana, Trikonasana, Paschimottanasana, Shavasana. Anulom-Vilom Pranayama, Bhramari Pranayama, meditation and Yoga Nidra, positively influenced physiological and biochemical markers linked to Hypertension such as autonomic nervous system activity, angiotensin II expression, oxidative stress, lipid metabolism, immune system function and inflammatory gene expression. Conclusion: The findings of this systematic review indicate that the Yoga practices have a positive impact on physiological and biochemical markers associated with hypertension which may help in its proper management and treatment. Future studies need to assess additional markers associated with hypertension, such as vasopressin, adrenocorticotropic hormone, gamma-aminobutyric acid and others to enhance the understanding of the mechanism of the effects of Yoga on hypertension. Study registration: PROSPERO ID: CRD42024497060.